Integrating ESG Metrics into Corporate Strategy: Analysing the Long-term Value and Profitability - Tania, Jenna; Permata Putri, Adhyva Wahyuningtyas; Muharam, Harjum (Research Horizon, 2025)
Research by McKinsey and the NYU Stern Centre for Sustainable Business indicates that robust ESG indicators are associated with enhanced returns and less negative risk. In Indonesia, firms possess a poor comprehension of the impact that integrating Environmental, Social, and Governance (ESG) measures into corporate strategy has on long-term value generation, resilience, and profitability. This study seeks to delineate the role of ESG in enhancing financial performance and sustainable growth within Indonesian firms. Researchers utilize purposive sampling to identify organizations that have consistently disclosed sustainability metrics in accordance with Environmental, Social, and Governance (ESG) requirements for a duration of five years. The population comprised 938 publicly listed companies on the Indonesia Stock Exchange (IDX), with 38 selected enterprises that consistently reported. This research does a comprehensive panel regression analysis using financial data sourced from the Bloomberg Terminal. The study reveals a complex relationship between Environmental, Social, and Governance disclosures and corporate financial success, particularly in emerging markets like Indonesia. It suggests that while firms prioritize governance transparency, its impact on financial performance may be temporary, affecting short-term profitability. Environmental and social disclosures, while positively connected with ROA, necessitate additional time or continuous application to yield financial benefits. The study emphasizes the imperative for a balanced and sustainable approach to Environmental, Social, and Governance integration in resource-constrained environments.